Watermelon Stomach, Hemorrhagic Pericarditis, Small Cell Carcinoma of the Lung and Synchronous Squamous Cell Carcinoma of the Tongue Base - Murinello, A (2012)
Based on a case of gastric antral vascular ectasia (watermelon stomach) that was associated with hemorrhagic pericarditis, small cell lung carcinoma with mediastinal lymph node metastases and a synchronous squamous cell carcinoma of the base of the tongue, the authors made a review of the clinical, endoscopic and histopathological aspects of this type of gastropathy, and its association with other diseases, and of the results of its endoscopic therapy. The causes of hemorrhagic pericarditis are considered, emphasizing the necessity to know if the effusion has a malignant etiology. To the best of our knowledge the association of watermelon stomach to small cell lung carcinoma and squamous cell carcinoma of the base of the tongue has not yet been described. Extensive metastases to mediastal lymph nodes are common to small cell lung carcinoma.